The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1017/s1751731115001627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole cottonseed v. sunflower seed on the fatty acid profile of subcutaneous fat, longissimus dorsi and blood of Thai Native and Holstein bulls

Abstract: In a 2 × 2 factorial design, 12 Thai Native and 12 Holstein bulls were fed ad libitum a total mixed ration (20 : 80; roughage : concentrate) with whole cottonseed (WCS) or sunflower seed (SFS) as oilseed sources. The rations contained 7% crude fat and were fed for 90 days. Plasma was taken at three times during the experiment, and at slaughter the longissimus dorsi and subcutaneous fat were sampled for fatty acid analysis. Ration did not affect rumen fermentation parameters. The plasma fatty acid profile was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
2
1
Order By: Relevance
“…Additionally, Wachirapakorn et al (2016) reported that cows fed ground corn cobs (33%) and rice straw (7%) in TMR, NDF digestibility was 63.40% and 52.60% respectively. However, for EE digestibility this experiment was approximately 86.36% lower than Polviset et al (2015) who suggested that 97.50% EE digestibility in Thai native bulls fed with sunflower seed. It might be reasoned that oil seeds may not negatively affect nutrients' digestibility.…”
Section: Apparent Digestibility Of Nutrientscontrasting
confidence: 69%
“…Additionally, Wachirapakorn et al (2016) reported that cows fed ground corn cobs (33%) and rice straw (7%) in TMR, NDF digestibility was 63.40% and 52.60% respectively. However, for EE digestibility this experiment was approximately 86.36% lower than Polviset et al (2015) who suggested that 97.50% EE digestibility in Thai native bulls fed with sunflower seed. It might be reasoned that oil seeds may not negatively affect nutrients' digestibility.…”
Section: Apparent Digestibility Of Nutrientscontrasting
confidence: 69%
“…Moreover, Kongmun et al (2011) suggestted that feeding of 7% coconut oil and 7% coconut oil plus garlic powder in swamp buffalo did not affect the DM, OM and ADF digestibility. Feeding sunflower seed and whole cotton seed in TMR contained 7% crude fat of Thai Native and Holstein bulls did not neither affect the digestibility of DM, OM, NDF and ADF by breed nor by different oilseed sources that oil seeds are less toxic than purified oils (Polviset et al, 2015). Additionally, adding soybean oil is harmful to microorganisms in the rumen and the fiber digestibility (Thanha et al, 2018).…”
Section: Chemical Composition Of Experimental Diets Nutrient Intake mentioning
confidence: 99%
“…There are some studies that investigated the addition of whole cottonseed (Costa et al, 2013;Polviset et al, 2015) and vitamin E in cattle diets (Machado Neto et al, 2014), however there are no studies that associated these ingredients with different lengths of finishing period affecting meat sensory traits and FA profile. To this end, this study evaluated how the addition of 30% DM whole cottonseed and 500 IU vitamin E in diets fed to Nellore bulls confined during 83, 104, and 111 days affected beef FA profile, and beef and hamburger sensory traits.…”
Section: Introductionmentioning
confidence: 99%